Factors affecting mortality of neonatal sepsis in Moewardi Hospital, Surakarta - Yulidar Hafidh; Dwi Hidayah; Sunyataningkamto Sunyataningkamto (Indonesian Pediatric Society Publishing House, 2007)
Background Mortality of neonatal sepsis is still a significant problem. It might be affected by many factors. Objective The purpose of this study was to determine factors which affect mortality of neonatal sepsis at neonatal ward of Moewardi Hospital, Surakarta. Methods Data of neonatal sepsis was obtained from medical records at the neonatal ward of Moewardi Hospital from December 2004 to November 2005. We recorded data from 97 neonatal sepsis consisted of 46 male and 52 female babies. Statistical analysis had been performed using univariate Chi-square and multivariate multiple logistic regression analysis. Results Overall neonatal sepsis mortality was about 40%. There were no significant difference in factors associated with mortality of neonatal sepsis such as gender (OR=0.44; 95% CI 0.19;1.014), referral patients (OR=1.61; 95% CI 0.195;.014), and bacterial growth culture (OR=1.96; 95% CI 0.856;4.44), except for birth weight which affected mortality (OR=6.29; 95% CI 2.57;15.42). Conclusion Birth weight affects mortality of neonatal sepsis in Moewardi Hospital. Patients with positive bacterial growth culture has two times higher risk of death, however, it is not statistically significant.